Physical activity and sedentary behaviour in 12-13 year old children, stratified by sex, school type and residential deprivation score - Davies, Emma Jane; Greenfield, J.R.F.; Edwards, K.L. (2016)
Many children are insufficiently active for good health. Factors affecting childhood physical activity and sedentary behaviour levels have been identified, including residential and school factors. Three schools in Sheffield, UK were recruited. Data were collected from children aged 12-13 years on their physical activity and sedentary behaviours using the Youth Physical Activity Questionnaire. Data were analysed using univariate (t-test), non-parametric (X2, Krusall Wallis), and regression models adjusted for school type, sex and residential deprivation score. Children (n=189) attending the independent schools had higher MVPA levels (p<0.008; 95% CI 348-2289 extra minutes per week), and were more likely to meet the physical activity guidelines; this association was particularly strong for boys (boys at independent schools 7.8x more likely). Sex and residential deprivation score were not statistically significantly associated with MVPA or meeting physical activity guidelines. Children in affluent areas had the highest sedentary behaviour levels (p=0.021; 95% CI -1171 to -98). School type and sex were not statistically significantly associated with sedentary behaviour, after adjusting for the other factors. This study found that independent school children, particularly boys, were more active across the whole day, when compared with their state school counterparts. They were also more likely to meet the government’s physical activity guidelines. There was no significant difference in the amount of time girls and boys spent in sedentary activities, but the types of sedentary activity differed between sexes. Children from less deprived areas reported more time spent in sedentary activities.